1998
DOI: 10.1017/s0007114598001093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of apparent ileal digestibility of amino acids and nitrogen in cottonseed and soyabean meals fed to pigs determined using ileal dissection under halothane anaesthesia or following carbon dioxide-stunning

Abstract: Two experiments were conducted to determine apparent ileal digestibility of amino acids (AIDAA) and nitrogen (AIDN) in cottonseed meal (CSM) and soyabean meal (SBM) fed to growing pigs. In the first experiment, twenty-four male pigs (37·3 (SE 2·7) kg) were individually penned and randomized to either CSM or SBM diets. The diets contained 40 % of the protein meal (either CSM or SBM) in a wheat starch-sucrose (1:1, w/w) base containing vitamins and minerals, and Cr 2 O 3 as an indigestible marker. Pigs were accl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
5
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
10
5
3
Order By: Relevance
“…The corresponding values for CSM were also close to some published values (Prawirodigdo et al, 1998;NRC, 2012), but lower than others (Almeida et al, 2014). The EAA SID values obtained in the present study were close to those reported in the NRC (2012), but lower than those reported by Sauvant et al (2004).…”
Section: Discussionsupporting
confidence: 89%
“…The corresponding values for CSM were also close to some published values (Prawirodigdo et al, 1998;NRC, 2012), but lower than others (Almeida et al, 2014). The EAA SID values obtained in the present study were close to those reported in the NRC (2012), but lower than those reported by Sauvant et al (2004).…”
Section: Discussionsupporting
confidence: 89%
“…The content of CP was relatively high while the contents of cell wall fractions were low, agreeing with previous reports (Tanksley et al, 1981; Batterham et al, 1990). The concents of CP in sources 1, 9, and 10 (50.85, 49.64, and 54.01%, respectively) were a little higher than previously published values (Tanksley et al, 1981; Batterham et al, 1990; NRC, 1998; Prawirodigdo et al, 1998; Li et al, 1999). The contents of ether extract in all of the CSM were much lower than excepted values (Tanksley et al, 1981; NRC, 1998), which indicates that more effective solvent had been used to extract the oil from cottonseed more entirely, and, as a result, the GE of the CSM were lower than the values obtained by Batterham et al (1990).…”
Section: Discussioncontrasting
confidence: 59%
“…The content of CP in sources 4, 5, and 8 (57.52%, 56.90%, and 56.78%, respectively) were much higher than previously published values (LaRue et al 1985;Papadopoulos et al 1987;Prawirodigdo et al 1998). The higher proportions of CP in these three CSM samples were likely due to the more advanced technology used for oil extraction of cottonseed.…”
Section: Chemical Composition Of Csm Sourcescontrasting
confidence: 52%